The fearful dental patient : a guide to understanding and managing - Weiner, Arthur A. (Ames, Iowa : Wiley-Blackwell, 2011)
'The Fearful Dental Patient: A Guide to Understanding and Managing helps the dental professional understand the basics of fears and phobias, how to identify dental phobia, and how to overcome it in cooperation with the patient. Dr. Weiner and his colleagues are all practicing dentists and provide proven diagnosis and treatment options. Chapters address basic concepts about patient fear, behavioral modalities to identify dental anxiety, modalities to manage dental fears, pharmacological and sedation techniques, and hypnosis. Chapters also discuss treating specific types of patients: those with psychiatric comorbidities, children, seniors, and special needs patients. The entire dental team will benefit from the practical presentation and proven methods to better understand and treat fearful patients'--Provided by publisher
Includes bibliographical references and index
Keywords: Dental Anxiety -- prevention & control; Dental Care -- psychology